2023
DOI: 10.1186/s12916-023-02734-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term air pollution exposure associated with death from kidney diseases: a nationwide time-stratified case-crossover study in China from 2015 to 2019

Abstract: Background Long-term exposure to air pollution has been associated with the onset and progression of kidney diseases, but the association between short-term exposure to air pollution and mortality of kidney diseases has not yet been reported. Methods A nationally representative sample of 101,919 deaths from kidney diseases was collected from the Chinese Center for Disease Control and Prevention from 2015 to 2019. A time-stratified case-crossover st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Plenty of studies have demonstrated that ambient air pollution, especially particulate matter (PM), has adverse impacts on almost every organ system including the kidney, a vital organ involved in hemofiltration and toxin excretion in the body . Emerging epidemiological studies suggest that ambient fine particulate matter (PM 2.5 ) and inhalable particles (PM 10 ) exposure is associated with an increased risk of CKD. However, these studies were limited to health effects on incidence, prevalence, death, or emergency room visits; little attention has been paid to the health effects on hospital admissions.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Plenty of studies have demonstrated that ambient air pollution, especially particulate matter (PM), has adverse impacts on almost every organ system including the kidney, a vital organ involved in hemofiltration and toxin excretion in the body . Emerging epidemiological studies suggest that ambient fine particulate matter (PM 2.5 ) and inhalable particles (PM 10 ) exposure is associated with an increased risk of CKD. However, these studies were limited to health effects on incidence, prevalence, death, or emergency room visits; little attention has been paid to the health effects on hospital admissions.…”
Section: Introductionmentioning
confidence: 90%
“…We coded them according to the International Statistical Classification of Diseases, Tenth Revision (ICD-10) (Table S1). ,, All CKD subtypes have enough hospital admissions for further analysis. In addition, information about gender, age, admission date, and length of hospital stay (LOS) was also obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second step, bilinear interpolation is used for the purpose of assessing the magnitudes of environmental variables, including PM 2.5 mass and its chemical components, temperature, and relative humidity, at the residential addresses of the patients prior to their hospitalisation. The detailed calculation process can be found elsewhere [ 26 , 27 ]. Briefly, this algorithm improved the spatial precision of environmental variables at particular locations through the calculation of a weighted average derived from the closest four grid points, and the weights were determined by the distance between the case address and the grids of meteorologic variables, with closer distances having higher weights [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…1 June, 15 June, 22 June, and 29 June) ( Shoraka et al, 2022 ). Therefore, the estimates represent the acute triggering effect of air pollution on the stroke hospitalization ( Cai et al, 2023c , Liu et al, 2022 ). This approach ensured that there are 3 or 4 control days matched to each stroke hospitalization (case day).…”
Section: Methodsmentioning
confidence: 99%